Implementasi Perbandingan Sistem Pengiriman Sinyal Suara secara Wireless pada Arduino - Muhammad Rasyid Perdana; Wijaya Kurniawan; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Technology has always experienced development from time to time, and the development of technology also affects various aspects of life, at this time the focus of how the impact of technology on audio media. Audio is the transmitter of information in the form of sound signals. with the development of technology now, not infrequently audio is used as a medium for delivering messages. In getting good sound quality, it is necessary to pay attention to several aspects that affect sound quality such as connecting media and the placement of sound sources and voice receivers. For this reason, this study designed a wireless voice sending device. This tool has a transmitter as sending voice and receiver as voice reception. For sending voice via radio media, the nRFL201 module is used, the HC-02 module is for sending voice via bluetooth, and the ESP8266 module is for sending voice over wifi. The module reading will be processed using the Arduino Uno micro controller. In each transmitter the mic will be used as the voice input and the speaker will use the speaker as the sound output. Based on the test results it shows a fairly large comparison when executing tools and programs together. The results of this test indicate that each sound signal that is sent has significantly different data. Every difference in distance, the data obtained has decreased. Whereas in bluetooth the sound signal produced is relatively stable. But there was a decrease in sound quality. For testing on wifi the results obtained by voice delivery are relatively stable. The sound quality produced is also consistent even though it is done at different distances.